2017
DOI: 10.1021/jacs.7b04755
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Germa-ketenimine on the Ge(100) Surface by Adsorption of tert-Butyl Isocyanide

Abstract: Reactions of the (100) surfaces of Ge and Si with organic molecules have been generally understood within the concept of "dimers" formed by the 2 × 1 surface reconstruction. In this work, the adsorption of tert-butyl isocyanide on the Ge(100)-2 × 1 surface at large exposures is investigated under ultrahigh vacuum conditions. A combination of infrared spectroscopy, X-ray photoelectron spectroscopy, and temperature-programmed desorption experiments along with dispersion-corrected density functional theory calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In addition, Table shows a splitting of 2.0 eV between the N (1s) of the 2C and 2N product, in agreement with the experimental 2.3 eV splitting found for N (1s), suggesting that the 2C structure downshifts the binding energies of the nearby atoms, so that the binding energy of unreacted N is closer to the observed 398.4 eV rather than near 400 eV values listed in Table . This shift is in correspondence with previous studies. , Further, based on the N (1s) splitting between 2N and 2C reported in Table , we assign the peak at 400.7 eV in the N (1s) spectra to nitrogen datively bonded to the surface. While both 1N and 2N adsorbates were found to have favorable bonding energies, the predicted splitting of ∼1 eV for the 1N product is inconsistent with the 2.3 eV splitting measured in the experimental N (1s) spectra.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Table shows a splitting of 2.0 eV between the N (1s) of the 2C and 2N product, in agreement with the experimental 2.3 eV splitting found for N (1s), suggesting that the 2C structure downshifts the binding energies of the nearby atoms, so that the binding energy of unreacted N is closer to the observed 398.4 eV rather than near 400 eV values listed in Table . This shift is in correspondence with previous studies. , Further, based on the N (1s) splitting between 2N and 2C reported in Table , we assign the peak at 400.7 eV in the N (1s) spectra to nitrogen datively bonded to the surface. While both 1N and 2N adsorbates were found to have favorable bonding energies, the predicted splitting of ∼1 eV for the 1N product is inconsistent with the 2.3 eV splitting measured in the experimental N (1s) spectra.…”
Section: Resultssupporting
confidence: 92%
“…This shift is in correspondence with previous studies. 102,103 Further, based on the N (1s) splitting between 2N and 2C reported in Table 3, we assign the peak at 400.7 eV in the N (1s) spectra to nitrogen datively bonded to the surface. While both 1N and 2N adsorbates were found to have favorable bonding energies, the predicted splitting of ∼1 eV for the 1N product is inconsistent with the 2.3 eV splitting measured in the experimental N (1s) spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…As part of this effort, Shong et al have reported a direct carbon-surface dative bond forming reaction on a Ge(100) surface. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…This result is in contrast with that for allyl alcohol adsorbed on Ge(100), for which the end-bridged configuration has a higher stability than the on-top structure by 0.07 eV/molecule (1.6 kcal/mol) . The paired end-bridged structure with four Ge–C bonds has previously been reported to be more favorable than the single end-bridged structure because of the stabilization of highly reactive radicals or zwitterionic characters on the dimer atoms that are not bound to adsorbates in the adsorptions of ethylene, norbornene, and styrene on Ge(100). This trend is consistent with the behavior found in the current study for vinyl alcohol on Ge(100).…”
Section: Resultsmentioning
confidence: 69%
“…The chemical modification of semiconductor surfaces via reaction with organic molecules has generated substantial interest because of its potential applications in the fabrication of molecule-based devices, biosensors, and organic dielectrics. The selectivity of the reaction pathway and the reaction site is crucial to such applications. Recently, solution-phase chemistry has been used to design new surface reactions under vacuum conditions to obtain specific substrate–adsorbate composite structures .…”
Section: Introductionmentioning
confidence: 99%